Identification of Specific Cellular Genes Up-Regulated Late in Adenovirus Type 12 Infection - Dorn, Andreas (American Society for Microbiology, 2005)
The infection of human cells by adenoviruses leads to a gradual reduction in the activity of host cell functions while viral gene expression progresses in a regulated way. We used the DNA microarray technique to determine the transcriptional activity profiles of cellular genes upon infection with adenovirus type 12 (Ad12). The microarray data were validated by quantitative real-time PCR for genes which showed significant alterations after Ad12 infection. At 12 h postinfection, there is a striking up-regulation between 10- and 30-fold in the expression of the G1P2, IFIT1, and IFIT2 cellular immune response genes compared to mock-infected cells. At later stages of infection, when the majority of regulated cellular genes has been turned down, a limited number of cellular genes exhibit increased activities by factors of 3 or less. These genes belong to the signal transduction or transcriptional regulator classes or are active in protein degradation, like ANPEP, an aminopeptidase. The SCD and CYP2S1 genes function in lipid metabolism. The eucaryotic translation initiation factor 4 is up-regulated, and one of the major histocompatibility complex genes is diminished in activity. For two of the genes, one up-regulated (CTSF gene) and one down-regulated (CYR61 gene), alterations in gene activity were confirmed at the protein level by Western blotting experiments. Increased genetic activity of cellular genes late in adenovirus infection has not been reported previously and demonstrates that Ad12 has a sustained control of host cell gene expression well into the late phase of infection.